Digital-Based Madrasah Curriculum Evaluation Model Islamic Framework in Facing Society 5.0 - Rian Atmajaya; Muhammad Zamzam (Civiliza Publishing, Indonesia., 2026)
Educational transformation in the era of Society 5.0 requires madrasahs to reconstruct their curriculum evaluation systems in order to adapt to intelligent technology integration while remaining grounded in Islamic values. This study aims to develop a Madrasah Curriculum Evaluation Model based on a Digital Islamic Framework as a response to the conceptual gap between conventional curriculum evaluation and the demands of a digital educational ecosystem. The research employed a Systematic Literature Review (SLR) approach guided by PRISMA, examining publications from 2015–2025 related to curriculum evaluation, Islamic education, digital transformation, and Society 5.0. The findings reveal that existing evaluation models remain administrative in nature, academically outcome-oriented, and insufficiently integrated with digital literacy and Islamic ethical dimensions. Through thematic synthesis, this study formulates a Digital Islamic Framework grounded in three core dimensions: theological-normative foundations, pedagogical-digital integration, and socio-transformative orientation. The model positions technology as a means for public benefit rather than an end in itself and reframes evaluation from mere outcome measurement into a strategic-reflective mechanism ensuring madrasahs’ readiness for digital civilization challenges. Theoretically, this study contributes to the advancement of integrative and future-oriented Islamic curriculum evaluation discourse. Practically, it offers a strategic reference for policymakers and madrasah leaders in designing adaptive, value-based evaluation systems.